Pengaruh Gaya Komunikasi Atasan Terhadap Kinerja Karyawan Pt. Indomarco Prismatama Di Yogyakarta - Farah Zuhaida Fatkhurrahman Putri; Katrin Narwas Rakhmasias (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study investigates the effect of supervisors’ communication styles on employee performance at PT Indomarco Prismatama Yogyakarta. Effective communication is essential for creating a productive work environment, while unclear and one-way communication may hinder employee performance. This research used a quantitative explanatory approach. Data were collected through questionnaires distributed to 108 active employees selected using purposive sampling. Data analysis was conducted using validity and reliability tests, normality and linearity tests, and simple linear regression analysis with SPSS version 27. The results show that all questionnaire items are valid and reliable, with Cronbach’s Alpha values of 0.941 for supervisors’ communication style and 0.955 for employee performance. The Kolmogorov–Smirnov test indicates that the data are normally distributed. Regression analysis reveals a significant positive effect of supervisors’ communication styles on employee performance, with a significance value of 0.001 (< 0.05). The coefficient of determination (R²) of 0.682 indicates that supervisors’ communication styles explain 68.2% of the variance in employee performance. These findings emphasize the importance of effective supervisory communication in improving employee performance.